Improvement Soil Biology Characteristics of Paddy Field by System of Rice Intensification - Widyatmani Sih Dewi (Faculty of Agriculture, Universitas Sebelas Maret, 2015)
The aim of the research was to test the System of Rice Intensification (SRI) method in improving the biological properties of paddy soil. The indicators of improvement were measured by the number of earthworm feces (cast), and the population of some microbial and nutrient content in the cast. The experiments were performed by comparing the three methods, namely: (1) SRI, (2) semi-conventional, and (3) conventional, using Randomized Completely Block Design. Each treatment was repeated nine times. The experiments were performed in the paddy fields belonging to farmers in Sukoharjo, Central Java. The result showed that the SRI (application of 1 tons ha-1 of vermicompost + 50% of inorganic fertilizer dosage) tends to increase the number of earthworms cast. It is an indicator of earthworm activity in soil. Earthworms cast contains more phosphate solubilizing bacteria (12.98 x 1010cfu) and N content (1.23%) compared to its surrounding soil. There is a close functional relation between earthworms cast with total tiller number. SRI method is better than the other two methods to improve the biological characteristics of paddy soil that has the potential to maintain the sustainability of soil productivity.